ESTIMASI FUNGSI PERMINTAAN DAN ELASTISITAS PERMINTAAN BRAND IMPORT THRIFT OLEH MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS UDAYANA - Suryawan, I Putu Eka; Yudha, I Made Endra Kartika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 14 No 2 (2025): Vol.14.No.2. FEBRUARI 2025 [123-196]DO - 10.24843/EEP.2025.v14.i02.p01, 2025)
The rising popularity of thrift clothing, particularly among students, highlights a shift in consumption behavior towards more affordable and environmentally conscious fashion choices. This trend is influenced by sustainable fashion and the limited budgets of students, often relying on allowances. Variables such as the price of second-hand and new clothes, as well as spending on fuel and phone credit, are crucial in understanding the demand for imported thrift brands. This study analyzes the impact of pocket money, the price of second-hand clothes, the price of new clothes, and fuel and phone credit consumption on the demand for imported thrift clothing among students at the Faculty of Economics and Business, Udayana University. Data was collected from 94 respondents using linear regression analysis. The results show that all independent variables significantly affect the demand for second-hand clothing, with an R² value of 72.1%. Specifically, pocket money, the price of second-hand clothes, and the price of new clothes have a significant positive impact on demand, while fuel and phone credit consumption do not. These findings suggest that students prefer thrift items as an affordable fashion alternative, offering valuable insights for stakeholders in shaping marketing strategies for fashion products